Mendorong Employee Pro-Environmental Behavior di Sektor Perbankan: Peran GHRM dan Green Psychological Climate sebagai Mediator - Ria Eka Sabellah; Ervita Safitri; Dinni Suci (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to examine the effect of Green Human Resource Management (GHRM) on Employee Pro-Environmental Behavior (EPEB) in the banking sector, with Green Psychological Climate (GPC) as a mediating variable. Drawing on the Ability-Motivation-Opportunity (AMO) Theory, the research investigates the mechanism through which GHRM practices translate into employees' pro-environmental behavior. A quantitative approach was employed using a cross-sectional survey design. Data were collected from all 85 employees of Bank Mandiri Palembang Kanwil Branch. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software.  The results reveal that GHRM does not have a significant direct effect on EPEB. However, GHRM significantly influences GPC and GPC, in turn, has a strong and significant effect on EPEB. Importantly, GPC fully mediates the relationship between GHRM and EPEB (β = 0.301, p < 0.05). The findings underscore that GHRM practices alone are insufficient to foster pro-environmental behavior unless they successfully shape employees' perceptions of a genuine organizational commitment to environmental sustainability. Practically, the study suggests that bank management should prioritize cultivating a strong green psychological climate to bridge the gap between green policies and actual employee behavior.